Establishing the nature of reversible cardiac remodeling in a rat model of hypobaric hypoxia-induced right ventricular hypertrophy - Van der Merwe, Aretha (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MSc (Physiological Sciences))--University of Stellenbosch, 2009.